Free Vibration of Partially Supported Cylindrical Shells. (1995) - Mirza, S.; Alizadeh, Y.
Abstract : The effects of detached base length on the natural frequencies and modal shapes of cylindrical shell structures were investigated in this work. Some of the important applications for this type of problem can be found in the cracked fan and rotor blades that can be idealized as partially supported shells with varying unsupported lengths. A finite element model based on small deflection linear theory was developed to obtain numerical solutions for this class of problems. The numerical results were generated for shallow shells and some of the degenerate cases are compared with other results available in the literature. The computations presented here involve a wide range of variables: material properties, aspect ratios, support conditions, and radius to base ratio.